Navigating Grief: The Resilience of Single Mothers in Facing Life Challenges After the Loss of a Spouse - Refadila Nur Apriliani; Fitrania Maghfiroh (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The death of a spouse is an event that not only causes deep grief but also forces women to undergo a role transition as single mothers who must cope with various demands simultaneously. This study focuses on the dynamics of resilience among single mothers as they navigate the grieving process and rebuild their lives following the death of their spouse. The objective of this study is to understand how single mothers make sense of their loss, adapt to life changes, and develop strategies to cope with the various challenges following their husband’s death. The study employs a qualitative approach using a case study design involving one single mother and two significant others selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The results revealed six main themes: (1) complex emotional dynamics in coping with the loss of a spouse; (2) challenges and coping strategies in managing the family’s finances; (3) social conflicts and their impact on family relationships; (4) the role of social and family support in building resilience; (5) the transformation of the single mother’s role in the life changes following her partner’s death; and (6) hopes and motivations for building a future for her children. The novelty of this study lies in the finding that single mothers’ resilience is a dynamic process that emerges through the management of grief, the reframing of life, and the transformation of their identity as heads of household. Resilience is formed through the acceptance of loss, religious and social coping mechanisms, and support from family and the community, enabling single mothers to bounce back, maintain their parenting and economic roles, and rebuild a sense of purpose in life.